2013
DOI: 10.2174/1874401x01306010087
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Morphological Variation in Two Common Marine Fish Species from South Africa

Abstract: Intraspecific morphological variation in fish is typically associated with sexual dimorphism, or one of three common environmental gradients: variation in intensity of predation, variation in water velocity, or variation in feeding niche. The preponderance of examples of environment-associated morphological variation within fish species has been documented in freshwater systems. It is not clear whether environment-associated intraspecific morphological variation is less common in marine fishes or whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Our morphometric measurements that were demonstrated in this study was a clear evidence of the hybrids' acquire of mix characteristics that came from both parent species (Majumder and Sharma, 1997). Mattson and Belk, (2013) presented different morphometric variations resulting from using different niches depending on the different resources in benthic and pelagic locations for A. inodorus which is a bento-pelagic species. Yet, gen flow is not an expected factor or is low effective for interspecies morphological variations for marine fish compared to fresh water fish (Mattson and Belk, 2013).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Our morphometric measurements that were demonstrated in this study was a clear evidence of the hybrids' acquire of mix characteristics that came from both parent species (Majumder and Sharma, 1997). Mattson and Belk, (2013) presented different morphometric variations resulting from using different niches depending on the different resources in benthic and pelagic locations for A. inodorus which is a bento-pelagic species. Yet, gen flow is not an expected factor or is low effective for interspecies morphological variations for marine fish compared to fresh water fish (Mattson and Belk, 2013).…”
Section: Discussionsupporting
confidence: 50%
“…Mattson and Belk, (2013) presented different morphometric variations resulting from using different niches depending on the different resources in benthic and pelagic locations for A. inodorus which is a bento-pelagic species. Yet, gen flow is not an expected factor or is low effective for interspecies morphological variations for marine fish compared to fresh water fish (Mattson and Belk, 2013). In this case, morphologic variations between marine fish require more investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that morphological divergences were associated with selective pressure exerted by the habitat where the populations lived. Intraspecific morphological variation in fish is typically related to sexual dimorphism or one of three typical environmental gradients: variation in predation intensity, water velocity, or feeding niche [20]. Concerning feeding niches, for instance, fish that feed on benthos tend to have a downturned mouth.…”
Section: Resultsmentioning
confidence: 99%